2007
DOI: 10.1262/jrd.18136
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characteristics of Porcine Fas-associated Death Domain (FADD) and Procaspase-8

Abstract: Abstract. To reveal the intracellular signal transduction molecules involved in granulosa cell apoptosis in porcine ovarian follicles, we cloned the porcine Fas-associated death domain (FADD), an adaptor protein for the cell death receptor, and procaspase-8, an initiator caspase. Porcine FADD (pFADD) was 636 bp (211 amino acids: aa) long and showed 74.0 and 65.4% homology with human and murine FADD, respectively. Porcine procaspase-8 (pprocaspase-8) was 1,431 bp (476 aa) long and 70.6 and 63.4% homologous with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Finally, caspase-3 activates endogenous endonuclease (caspase activated DNAse: CAD), resulting in apoptosis. In pig ovaries, procaspase-8 protein is expressed in granulosa cells, and cleaved procaspase-8, the active form, is detected in atretic follicles [15][16][17]. TRADD is not detected in the granulosa cells of healthy follicles, but it is highly expressed in atretic follicles [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, caspase-3 activates endogenous endonuclease (caspase activated DNAse: CAD), resulting in apoptosis. In pig ovaries, procaspase-8 protein is expressed in granulosa cells, and cleaved procaspase-8, the active form, is detected in atretic follicles [15][16][17]. TRADD is not detected in the granulosa cells of healthy follicles, but it is highly expressed in atretic follicles [18].…”
mentioning
confidence: 99%
“…TRADD is not detected in the granulosa cells of healthy follicles, but it is highly expressed in atretic follicles [18]. Another adaptor protein, FADD, is also present in pig granulosa cells [17]. Moreover, the caspase-9 precursor (procaspase-9) decreases, while caspase-9 activity increases as follicular atresia progresses [19].…”
mentioning
confidence: 99%
“…The TNFα-mediated apoptotic signaling pathway (TNFR1-dependent apoptosis) has been suggested to be as follows [1][2][3][4][5][6][7][8] In mammalian ovaries, more than 99.9% of follicles undergo a degenerative process known as "atresia", and only a few follicles selectively ovulate during ovarian follicular development and growth [15][16][17][18][19][20][21]. Our recent findings [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] have suggested that apoptosis in follicular granulosa cells plays a crucial role in the regulation of ovarian follicular atresia; however, the intracellular signal transduction pathway for apoptois in granulosa cells is still largely unknown [20,21]. Moreover, we have previously suggested that apoptosis and proliferation in granulosa cells are dominantly regulated by a cell death ligand and receptor system (TNF and TNFR superfamily members) [18][19][20][21].…”
mentioning
confidence: 99%
“…Bars=100 μm. [50][51][52][53][54][55][56][57][58]. Their participation in the apoptosis of granulosa cells and follicular atresia has been suggested, although their significance in the regulation of follicular atresia in vivo remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that follicular cells have certain inhibitors of Fas-mediated apoptosis. There are several reports on anti-apoptotic factors in ovarian follicles, including Fas-associated phosphatase (FAP-1) [45], members of the inhibitor of apoptosis protein (IAP) family [46][47][48][49] and cellular FLICE-like inhibitory protein (c-FLIP) [50][51][52][53][54][55][56][57][58]. Their participation in the apoptosis of granulosa cells and follicular atresia has been suggested, although their significance in the regulation of follicular atresia in vivo remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%